Isothermal Elasto-hydrodynamic Lubrication Analysis of the Roller Enveloping End Face Meshing Worm Drive - Xiaolong Wang; Honghui Liao (Jixie chuandong)
Based on the transmission theory of single roller enveloping end face meshing worm drive and isothermal elastohydrodynamic lubrication theory， and considering the influence of surface wavy roughness， a numerical analysis method is adopted to analyze the influence of different meshing positions， roughness amplitude， roller radius and throat diameter coefficient on the elastohydrodynamic lubrication performance of transmission pair. The results show that the lubrication performance is the worst at the top of the worm gear at the meshing position of the transmission pair， and the increase of roughness amplitude， roller radius and throat diameter coefficient has a positive effect on the lubrication performance， and makes the oil film thickness increase and the oil film pressure decrease.